Faith, finance, and fintech: Unraveling the drivers of student consumptive behavior through lifestyle - Saputra, Apriyan; Rafidah, Rafidah; Apriani, Alfia (Universitas Negeri Surabaya, 2025)
Various factors—including digital payment usage, financial literacy, religiosity, and lifestyle—influence consumptive behavior. This study investigates the impact of digital payments, Sharia financial literacy, and religiosity on the consumptive behavior of students at UIN Sultan Thaha Saifuddin Jambi, with lifestyle acting as a mediating variable. The research utilizes descriptive statistical analysis and Structural Equation Modeling with Partial Least Squares (SEM-PLS). The study population consists of 19,307 active students enrolled at UIN Sultan Thaha Saifuddin Jambi during the odd semester of the 2024/2025 academic year. The sample size was determined using Hair’s formula, and data were collected through proportionate stratified random sampling and purposive sampling techniques. The findings indicate that digital payments have a positive and significant effect on both lifestyle and consumptive behavior. Lifestyle, in turn, positively and significantly influences consumptive behavior. Sharia financial literacy has a positive and significant effect on lifestyle but a negative and significant effect on consumptive behavior. Religiosity positively and significantly affects both lifestyle and consumptive behavior. Furthermore, digital payments, Sharia financial literacy, and religiosity exert a positive and significant indirect influence on consumptive behavior through lifestyle as a mediating variable..